THE ROLE OF GUT MICROBIOTA IN RHEUMATIC DISEASES: CURRENT EVIDENCE AND FUTURE DIRECTIONS - Michał Ględa; Aleksandra Grygorowicz; Klaudia Baran; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Kamil Jabłoński; Anna Woźniak (International Journal of Innovative Technologies in Social Science, 2025)
The gut microbiota plays a fundamental role in sustaining physiological homeostasis, and its disruption–referred to as dysbiosis – has been increasingly associated with the pathogenesis of autoimmune disorders, including rheumatic diseases. Growing evidence underscores the complex bidirectional interactions between the gut microbial community and the host immune system, interactions that may critically influence the initiation and progression of conditions such as rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), and psoriatic arthritis (PsA).This review synthesizes current knowledge on the relationship between gut microbiota composition and rheumatic disease, with particular emphasis on the underlying immunological mechanisms. It delineates characteristic alterations in microbial profiles reported in patients with selected rheumatic conditions and evaluates how such perturbations may shape immune responses.Furthermore, the paper examines emerging therapeutic strategies aimed at modulating the gut microbiota, including probiotics, prebiotics, targeted dietary interventions, and the increasingly explored approach of fecal microbiota transplantation (FMT). By critically assessing existing evidence, the review addresses the efficacy and safety of microbiota-centered interventions and outlines prospective avenues for their integration as adjunctive therapies in rheumatic disease management.